(untitled) (International Journal of World Civilizations and Philosophical Studies, 2025)
This study analyzes the existence of a capitalist system in industrial companies in Malang, Indonesia. This research uses a qualitative approach with a case study type. The study consisted of primary and secondary data. Observations and interviews are primary data, while journal and book research results are secondary data. The subject determination technique uses purposive sampling, and the data analysis technique uses the Miles and Huberman model (data collection, data reduction, data presentation, and conclusion drawn). A data validity technique with source triangulation resources. The theoretical analysis implements Karl Marx's theory of class, human beings, and surplus values, concluding with an inductive or generalizing pattern. The results of the study stated that capitalism in industrial companies in Malang, Indonesia, was caused by the implementation of labor and corporate social responsibilities similar to the slavery system. Such as wages that are not by the minimum wage, BPJS charged to workers, BPJS workers must work for at least 2 years, and health insurance that only applies to "slave" submissive workers.